2021
DOI: 10.3390/genes12121935
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Amyotrophic Lateral Sclerosis: A Review

Abstract: Juvenile amyotrophic lateral sclerosis (JALS) is a rare group of motor neuron disorders with gene association in 40% of cases. JALS is defined as onset before age 25. We conducted a literature review of JALS and gene mutations associated with JALS. Results of the literature review show that the most common gene mutations associated with JALS are FUS, SETX, and ALS2. In familial cases, the gene mutations are mostly inherited in an autosomal recessive pattern and mutations in SETX are inherited in an autosomal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 78 publications
0
34
0
Order By: Relevance
“…A rare and expanding subgroup of such cases includes juvenile ALS (JALS), with onset of motor compromise before age 25. JALS is commonly misdiagnosed and underrecognized in clinical practice, mainly due to low disease awareness and several diagnostic misconceptions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rare and expanding subgroup of such cases includes juvenile ALS (JALS), with onset of motor compromise before age 25. JALS is commonly misdiagnosed and underrecognized in clinical practice, mainly due to low disease awareness and several diagnostic misconceptions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 30 years, more than ten causative genes have been identified in JALS. [3] The SPTLC1 gene encodes the long-chain base subunit one of serine palmitoyltransferase (SPT), which is the critical rate-limiting enzyme in the initial step of sphingolipid biosynthesis. [4] In 2001, SPTLC1 was identified as the causative gene for hereditary sensory neuropathy type 1 (HSAN1), [5] and mutations identified in patients with HSAN1 reduced SPT activity, leading to the accumulation of pathogenic and neurotoxic sphingolipids.…”
Section: Introductionmentioning
confidence: 99%
“…It is universally known that genetics play significant roles in the pathogenesis of JALS. Over the last 30 years, more than ten causative genes have been identified in JALS [3] …”
Section: Introductionmentioning
confidence: 99%
“…One of the main differences between adult-onset ALS and JALS is their genetic background, with a higher contribution of genetic causes detected in JALS (40%) than in adult-onset ALS (around 10%) [ 2 , 6 , 7 ]. The frequencies of associated genes are also different between the two forms of onset.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of associated genes are also different between the two forms of onset. A recent review of JALS [ 7 ] identified FUS (fused in sarcoma), SETX (Senataxin), and ALS2 (Alsin) as the most common genes reported in the literature. In contrast, pathogenic variants in genes commonly associated with adult forms, such as SOD1 (copper–zinc superoxide dismutase) or TARDBP (transactive response DNA-binding protein), were reported less frequently, and C9orf72 (chromosome 9 open reading frame 72), the most prevalent inherited gene in adult disease, has not been reported in childhood [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%